DEVELOPMENT OF ENHANCED MIXED MATRIX MEMBRANES BY USING ALKANOLAMINE SOLUTION FOR C02/CH4 SEPARATION - NASIR, RIZW AN (2015)
Poor performance of mixed matrix membranes (MMMs) is due to agglomeration of fillers and weak adhesion between the fillers and the polymer matrix. The main objective of this study is to synthesize enhanced MMM consisting polyethersulfone (PES), carbon molecular sieve (CMS) and di-ethanolamine (DEA) which is having high carbon dioxide (C02 ) affinity for improvement of membrane morphology and performance. Various loadings ofCMS (10-30 wt. %) and concentrations ofDEA (5- \5 wt. %) was incorporated into PES sol to synthesize enhanced MMMs. The membranes morphology, physicochemical, thermal and mechanical properties were analysed systematically. The performance of these membranes was evaluated and measured in terms of permeance and selectivity. The morphological evaluation showed the dense. non-porous structure. in which the CMS and DEA were uniformly distributed within the polymer matrix.